Optimizing Employee Performance through Compensation and Work Motivation: The Mediating Role of Job Satisfaction - Mohamad Ilham Saputra; Irawan Yuswono (Global Health Science Group, 2026)
This study examines the effects of compensation and work motivation on employee performance, with job satisfaction as a mediating variable, in Kedai Minumku MSME in Semarang City. A quantitative causal approach was applied using a census sampling technique involving 102 employees. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results show that compensation and work motivation have positive and significant effects on job satisfaction and employee performance. Work motivation has a stronger influence on job satisfaction, indicating that intrinsic factors play a more dominant role in shaping employee attitudes. In addition, job satisfaction significantly affects employee performance and partially mediates the relationships between compensation and performance, as well as motivation and performance. These findings suggest that improving employee performance in MSMEs requires a balanced approach between financial compensation and motivational strategies. While compensation ensures fairness and stability, motivation and job satisfaction contribute more strongly to employee engagement and productivity. Therefore, MSME owners are encouraged to create a supportive work environment while maintaining fair compensation systems to achieve optimal performance.